Constitutional oath of judges: a comparison with Australia, UK, US, and India - Ramalingam, Chithra Latha; Ali Mohamed, Ashgar Ali; Ahmad, Muhamad Hassan (Lexis Nexis Malaysia Sdn Bhd, 2021)
Having said the above, this article discusses the constitutional oath of judges with reference to its practice in United Kingdom, United States of America, India and Australia.